2022
DOI: 10.33963/kp.a2022.0098
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of clinical characteristics of cardiac amyloidosis as a potential underlying etiology in patients diagnosed with heart failure with preserved ejection fraction

Abstract: Background: Heart failure with preserved ejection fraction (HFpEF) is heterogeneous clinical syndrome. Transthyretin cardiac amyloidosis (CA) is an underdiagnosed cause of HFpEF. Red flags are extremely useful for suspecting CA. Aims:We aimed to evaluate the frequency of cardiac and extracardiac manifestations of CA in HFpEF patients based on red flags.Methods: Baseline characteristics of 85 patients were recorded during admission. Electrocardiogram and echocardiography were performed. All patients were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…A recent prospective, observational, single-center study from Turkey that aimed to evaluate the frequency of cardiac and extracardiac manifestations of CA in patients with heart failure with HFpEF based on red flags also confirms the necessity of timely expert center referrals as the study reported that patients diagnosed with HFpEF had an average of 1.3 red flags suggestive of CA (D-14). The same study also reported that patients with ATTR-CA had twice as many red flags as those without (2.46 vs. 1.04), and ATTR-CA diagnosis was more common in patients with 2 or more red flags ( 14 ).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A recent prospective, observational, single-center study from Turkey that aimed to evaluate the frequency of cardiac and extracardiac manifestations of CA in patients with heart failure with HFpEF based on red flags also confirms the necessity of timely expert center referrals as the study reported that patients diagnosed with HFpEF had an average of 1.3 red flags suggestive of CA (D-14). The same study also reported that patients with ATTR-CA had twice as many red flags as those without (2.46 vs. 1.04), and ATTR-CA diagnosis was more common in patients with 2 or more red flags ( 14 ).…”
Section: Discussionmentioning
confidence: 71%
“…Another multicenter, national, observational study examined 886 patients who applied to the cardiology clinics in 22 centers managed to identify 15 (1.69%) patients with CA who were diagnosed by endomyocardial biopsy (13). A prospective, observational, single-center study from Turkey also reported 15 patients (17.6%) with a positive specific scintigraphy result, confirming the presence of ATTR-CA among 85 patients with heart failure with preserved ejection fraction (HFpEF) (14).…”
Section: Introductionmentioning
confidence: 90%
“…A previously published study with a smaller cohort of HFpEF patients reported that echocardiographic red flags were detected in six out of every ten patients with TTR-CA. 25 Among these red flags, unexplained left ventricular hypertrophy (LVH) is one of the most important findings, as it raises the clinician's suspicion of TTR-CA during the echocardiographic evaluation of a patient with HFpEF. Previous studies have reported that the prevalence of TTR-CA in patients with LVH ranges between 13% and 19%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the prevalence of TTR-CA in patients with LVH ranges between 13% and 19%. [25][26][27][28] While LVH is recognized as an important finding, a recent study found that the prevalence of CA in HFpEF patients without LVH was 5.2%. 24 In contrast, our study did not obtain any grade 2 or 3 99mTc-PYP scintigraphy results in HFpEF patients lacking LVH, and none of these patients were diagnosed with TTR-CA.…”
Section: Discussionmentioning
confidence: 99%
“…As LVEF remains normal or slightly decreased in RCM patients for a long time [2], it is important to include amyloidosis [22] and na-RCM in differential diagnosis of HF with preserved ejection fraction. Although LVEF is commonly used in clinical practice, it is less suitable for assessing prognosis in RCM than RV function.…”
Section: Discussionmentioning
confidence: 99%